Removal of organic compounds by nanoscale zero-valent iron and its composites - Li, Qian; Chen, Zhongshan; Wang, Huihui; Yang, Hui; Wen, Tao; Wang, Shuqin; Hu, Baowei; Wang, Xiangke (The Science of the total environment, 2021)
During the latest several decades, the continuous development of the economy and industry has brought more and more serious organic pollutants to the natural environment, which have inevitably aroused severe menace to human health and the environmental system. The nano zero-valent iron (NZVI) particles and NZVI-based materials have widely applied to remove organic pollutants. This article reviews the key advancements of different methods for the synthesis of NZVI and NZVI-based materials. Different modification methods (e.g., doped NZVI, encapsulated NZVI and supported NZVI) are also introduced detailedly for overcoming the defects of NZVI such as aggregation and easy oxidation. The removal of different organic pollutants including dyes, halogenated organic compounds, nitro-organic compounds, phenolic compounds, pesticides, and antibiotics are summarized. The interaction mechanisms, including adsorption, reduction, and active oxidation of organic pollutants by NZVI/NZVI-based composites, are discussed. The dyes are mainly removed by destroying their chromogenic group according to the reduction or the Fenton-like reaction with NZVI. The removal of halogenated organic compounds (HOCs) is realized by the dehalogenation process, including reductive elimination, hydrogenolysis, and hydrogenation. As for the nitro-organic compounds, three different reduction pathways as nitro-reduction (into amino), cleavage at the carbon‑nitrogen bond or denitration of the NO2 group may take effect. The phenolic compounds can be mineralized into inorganic molecules, including CO2 and H2O, by Fenton oxidation. This review might provide the basis for future studies on developing more effective NZVI-based materials for the treatment of wastewaters contaminated by organic pollutants. [Display omitted] •Synthesis and modification of NZVI and NZVI-based composites were summarized.•Removal of organic pollutants by NZVI and NZVI-based composites were reviewed and compared.•The interaction mechanism was discussed from spectroscopy analysis and theoretical calculation.•The challenges and perspectives for NZVI-based composites were discussed.